See you next year - Larsen, Andrew, 1960- (Owlkids Books Inc., 2015)
Summer vacations can be magical. Especially when you go back to the same place every year. A place where you can learn to dive under the waves. A place where digging a hole to the center of the earth seems possible. A place where nothing ever changes and where each long, lazy day unfolds just as it did the year before. See You Next Year is the story of one such place. Only this year, something does change. And sometimes, change turns out to be a good thing.